Key account manager's internal selling role : an exploration of interpersonal conflict - Speakman, James Ian Forbes (Cranfield University, 2008)
Acting in a boundary spanning role within their organisations, the key account manager in representing their customers’ needs internally is required to manage a wide range of complex internal relationships. This can often lead to incidents of conflict between the key account manager and other individuals or groups of individuals within the organisation in non-sales functions. Using the Critical Incident Technique (CIT), (Flanagan, 1954) together with an interpretive framework for data coding (Spiggle, 1994), this research investigates conflict and the key account manager’s internal selling role. This research also explores how the key account manager perceives intraorganisational, interpersonal conflicts and investigates the complex behavioural sequences adopted to manage them. In doing so this research addresses some of the shortcomings of the traditional view of the nature of organisational conflict and how it is managed while extending our understanding of the key account manager’s internal selling role. In contrast to the majority of research into personal selling, this research takes an interpretive approach through the analysis of transcripts from a series of CIT interviews with key account managers in the field. Twenty-nine key account managers from seven participating FMCG, Blue Chip organisations in the U.K. and U.S. participated in the research. From the CIT interviews conducted, 112 critical incidents were described with both positive and negative outcomes. This research provides further insight into the complexity of conflict, suggesting conflict is inherent within the key account management internal selling role, that incidents of conflict do not occur in isolation, that these conflict episodes are complex, having multiple components and that a combination of behaviours can be used in their management. In addressing these issues in the key account management context, this research further develops our knowledge of personal selling and the key account manager’s internal selling role by providing an analysis of the recollections of how conflict is perceived and managed by the key account managers involved.